Réponses

2014-03-02T17:20:55+01:00
A = 3 ( x - 2 ) + 5 ( 3 - x )
A = 3x - 6 +15 - x
A = 3x - x + 15 - 6
A = 2x + 9

B = x ( 3 + x ) - 2 ( x + 5 )
B = 3x + x² - 2x - 10
B = x² + 3x - 2x - 10
B = x² + x - 10

C = -2 ( x - 7 ) - 2 ( x² + x ) + 4 ( x² + 1 )
C = -2x + 14 - 2x² - 2x + 4x + 4
C = -2x² + 18
G = 2(-x² + 9 )

D = 2x ( -x + 5 ) - x² ( 1 - x )
D = -2x² + 10x - x² + x³
D = x³ - 3x² + 10x
D = x ( x² - 3x + 10 )

E = 6x( 2x² - 3x ) - 3 ( x + 4x² ) - x ( -3 + 4x )
E = 12x³ -18x² - 3x - 12x² + 3x - 4x²
E = 12x³ - 18x² - 12x² - 4x² - 3x + 3x
E = 12x³ - 34x²
E = 2x² ( 6x - 17 )